Post-Traumatic Growth Pada Wanita Yang Mengalami Toxic Relationship Menurut Perspektif Psikologi Islam - Wahyunnisa Aisy Agustini; Anniez Rachmawati Musslifah (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to investigate the phenomenon of Post-traumatic growth (PTG) in women who experience toxic relationships according to an Islamic Psychology perspective. PTG refers to the positive changes and growth that emerge after a traumatic experience, and this research focuses on how women who have been involved in toxic relationships experience positive growth in accordance with the teachings and principles of Islamic Psychology. This research will use a qualitative approach with in-depth interview methods with a number of women who have experienced toxic relationships. Additionally, text and content analysis will be used to identify patterns of positive growth that emerge from these traumatic experiences. The collected data will be analyzed by referring to Islamic psychological concepts such as patience, trust, and muhasabah. It is hoped that the results of this research will provide a deeper understanding of how women experience positive growth after experiencing a toxic relationship, as well as how the principles of Islamic Psychology, such as trust and patience, play an important role in this process. The implications of this research can contribute to the development of a more holistic psychotherapy approach based on Islamic values to help someone overcome traumatic experiences and achieve positive growth.